Lipoperoxidation and cyclooxygenase enzyme inhibitory piperidine alkaloids from Cassia spectabilis green fruits - Viegas, Claudio [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Pivatto, Marcos [UNESP]; de Rezende, Amanda [UNESP]; Castro-Gamboa, Ian [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Nair, Muraleedharan G. (Amer Chemical Soc, 2007)
Phytochernical work in the search for bioactive metabolites from the methanolic extract of Senna spectabilis green fruits led to the isolation of a new piperidine alkaloid, (+)-3-O-feruloylcassine (1), in addition to the known (-)-spectaline (2) and (-)-3-O-acetylspectaline (3). The isolates were submitted to in vitro evaluation of lipoperoxidation (LPO) and cyclooxygenase enzymes (COX-1 and -2) inhibitory properties and showed moderate antioxidant activities (40-70%) at 100 ppm when compared to commercial standards BHT and vitamin E and moderate inhibition of COX-1 (ca. 40%) and marginal inhibition of COX-2 enzymes (< 10%) at 100 ppm when compared to nonsteroidal anti-inflammatory drugs (NSAIDs) aspirin, rofecoxib, and celecoxib, respectively.